KEPERCAYAAN INVESTOR TERHADAP KINERJA PERBANKAN GO PUBLIC DI BURSA EFEK JAKARTA - Maya Indriastuti; Indri Kartika (Jurnal Keuangan dan Perbankan, 2008)
Monetary crisis in Indonesia had given wide influence on Indonesia Businesscondition. There was money crisis in many companies, including banking firms, that affectedlower public confidence. This study examined the influence of financial performance thatwas represented by the financial ratio to the stock price. There were10 financial ratios thatpredicted influence stock price. Data in this study wais collected from 11 go-public bankingcompanies in Jakarta Stock Exchange in 2001- 2005 by using purposive sampling method. Thefactor analysis was used to identify dimension of each variable, and regression analysis wasused to test the hypothesis. The empirical result showed that simultaneously, all financialratios influenced to stock price. Partially, only two ratios affected the stock price.